Desi hoop dreams : pickup basketball and the making of Asian American masculinity - Thangaraj, Stanley I. (New York University Press, 2015)
South Asian American men are not usually depicted as ideal American men. They struggle against popular representations as either threatening terrorists or geeky, effeminate computer geniuses. To combat such stereotypes, some use sports as a means of performing a distinctly American masculinity. Desi Hoop Dreams focuses on South Asian-only basketball leagues common in most major U.S. and Canadian cities, to show that basketball, for these South Asian American players is not simply a whimsical hobby, but a means to navigate and express their identities in 21st century America. The participatio.